2019
DOI: 10.1002/anie.201905021
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Dearomativesyn‐1,4‐Carboamination with Grignard Reagents

Abstract: Ap rotocol for palladium-catalyzed dearomative functionalization of simple,nonactivated arenes with Grignard reagents has been established. This one-pot method features avisible-light-mediated [4+ +2] cycloaddition between an arene and an arenophile,and subsequent palladium-catalyzed allylic substitution of the resulting cycloadduct with aG rignard reagent. Av ariety of arenes and Grignard reagents can participate in this process,f orming carboaminated products with exclusive syn-1,4-selectivity.M oreover,t he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 97 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…In 2019, a protocol involving the key excited complex of arenes and MTAD for palladium-catalyzed dearomative functionalization of simple, nonactivated arenes with Grignard reagents was established (Scheme 59). 105 Followed the dearomative visible-light induced [4+2] cycloaddition, a palladiumcatalyzed allylic carbonation was engaged with a variety of alkyl-and aryl-Grignard reagents to afford 1,4-carboaminated products. To demonstrate the practical synthetic utility of this protocol, a series of product diversifications were conducted, as well as the concise synthesis of sertraline from simple naphthalene.…”
Section: Direct Photo-activation Of the Reaction Partnersmentioning
confidence: 99%
“…In 2019, a protocol involving the key excited complex of arenes and MTAD for palladium-catalyzed dearomative functionalization of simple, nonactivated arenes with Grignard reagents was established (Scheme 59). 105 Followed the dearomative visible-light induced [4+2] cycloaddition, a palladiumcatalyzed allylic carbonation was engaged with a variety of alkyl-and aryl-Grignard reagents to afford 1,4-carboaminated products. To demonstrate the practical synthetic utility of this protocol, a series of product diversifications were conducted, as well as the concise synthesis of sertraline from simple naphthalene.…”
Section: Direct Photo-activation Of the Reaction Partnersmentioning
confidence: 99%
“…[19] Interestingly, using palladium as a catalyst, we found that the selectivity of the dearomative carboamination with Grignard reagents occurred exclusively with syn-1,4-selectivity. [20] The reaction with benzene proceeded smoothly with a wide variety of aryl, vinyl, and alkyl Grignard reagents, and the scope of the arenes was extended to various monocyclic and polycyclic arenes (Scheme 8A, conditions A and B). The synthetic utility of this process was demonstrated by the preparation of Sertraline (47), [21] one of the most prescribed antidepressants, from naphthalene (Scheme 8B).…”
Section: Transition-metal-catalyzed Dearomative Aminofunctionalizationmentioning
confidence: 99%
“…Reduction of an N‐Boc‐protected primary amine with LAH is a well‐applied method to obtain the N‐methyl product. Table presents three recent examples using LAH or LiAlH(OMe) 3 as the reductant for the reduction of carbamates or ureas.…”
Section: N‐methylationmentioning
confidence: 99%